(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
After two decades of formulation of the National Telecom Policy (NTP) in 1999, The Indian telecom industry is passing through complex times. The mobile phone has transformed into a persuasive medium to deliver information services spanning various usage areas such as governance, commerce, agriculture, education, and health. Standing tall by being the second-largest telecommunications market in the world next to china, the industry has now billion-plus subscribers. Comprising major sectors like telephony, internet, and broadcasting the industry is contributing significantly to the country’s GDP and job growth. The lowest tariffs, Mobile portability, and various services have resulted in a dynamic and hyper-competitive market. With a ferocious battle taking place between the established biggies and the new entrants the companies that will survive the competition will be the ones being able to differentiate themselves on the basis of service quality. In today’s competitive environment customer occupies the central place in business & retaining a satisfied customer can pay more compared to attracting a new one. Considering India at the cusp of a data revolution and telecom as the backbone this study examines the impact of service quality and service value on customer bonding. The study aims to provide a better understanding and analyze the gap in service quality of the Telecom sector in terms of customers’ expectations and perceptions using SERVQUAL and other models.